STUDI KELOMPOK SOSIAL PADA SISWA SMA NEGERI 6 PEKANBARU - Fadliyanti, Novia; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Social group is a collection of people who have a common awareness and membership will interact with each other. Social group or entity in the form of a set of people who live together, because of the relationship between them. The other concerns the relationship between the reciprocal relationship of mutual influence and also an awareness to help each other. Social groups can be formed by various groups, including social groups among students. The purpose of this study is (1) to explain the emergence of social groups on the student, (2) to explain the process of formation of social groups on students. Students are teenagers aged 15 to 19 years, which at that age is a time for someone to show his identity by showing works on attitude. The method used qualitative and researchers take sampling using the snowball method and researchers gain of respondents were 52 students who form a social group. Types of groups that exist in schools varied, depending on the differences between students who are in school, there are based on a common vision, recreational interests, and in support of access such as vehicles, communication devices including mobile phones and smartphones and facilities including textbooks, sports fields, sports equipment and art tools. Factors common vision, recreational interests, and in support of access is an important factor in the formation of the group.Keywords: Social Group, Students